Lung Cancer in Homeless People: Clinical Outcomes and Cost Analysis in a Single Institute - Koung Jin Suh; Ki Hwan Kim; Jin Lim; Jin Hyun Park; Jin-Soo Kim; In Sil Choi (Canadian Respiratory Journal)
Introduction. To characterize the demographic and clinical features, outcomes, and treatment costs of lung cancer in homeless people. Methods. Medical records of 22 homeless patients with lung cancer at Seoul National University Boramae Medical Center in Seoul, South Korea, were retrospectively analyzed. Results. All patients were men (median age, 62 years). Most patients (78%) had advanced disease (stage IIIB, n=2; stage IV, n=15). Seven died during initial hospitalization (median survival, 1.5 months). Six were lost to follow-up after initial outpatient visits or discharges from initial admission (median follow-up, 13 days). Only 4 received appropriate treatment for their disease and survived for 1, 15, 19, and 28 months, respectively. Conversely, 4 of 5 patients with early stage disease (stage I, n=4; stage IIA, n=1) received curative surgery (median follow-up 25.5 months). The median treatment cost based on 29 days of hospitalization and 2 outpatient visits was $12,513, constituting 47.3% of the 2013 per capita income. Inpatient treatment accounted for 90% of the total costs. The National Health Insurance Service paid 82% of the costs. Conclusion. Among the homeless, lung cancer seems to be associated with poor prognosis and substantial costs during a relatively short follow-up and survival period.